Constitutive Duality: A Bourdieusian Analysis of Arab-Islamic NGO Philanthropy in Senegal - Alassane Sow; Kamali Kamali; Imam Buchari (Surau Journal of Islamic Studies, 2026)
This study examines the constitutive duality of Arab-Islamic NGO philanthropy in Senegal, where the same actions simultaneously fill public service gaps and reshape religious authority. While over 500 such organizations operate in Senegal, building mosques, schools, and wells, their impacts remain undertheorized beyond binary categories of aid versus interference. A multi-sited ethnographic case study was conducted over six months across Dakar, Touba, Kaolack, and Matam, employing semi-structured interviews with five key informants, participant observation, documentary analysis, and Social Network Analysis. The findings reveal that the same mosque built with Gulf funding is simultaneously framed as charity (by NGOs), regulation (by the state), ideological competition (by Sufi brotherhoods), and social mobility opportunity (by youth). Using Bourdieu’s field theory, the study argues that this constitutive duality is a structural feature of Senegal’s religious field in transition from doxa to heterodoxy, where colliding habitus and unequal capital produce multiple, simultaneous meanings. The study concludes that transnational Islamic philanthropy cannot be reduced to binary categories. It must be understood as a complex process where welfare and authority, complementarity and competition, cooperation and transformation are produced simultaneously. This reframing has significant policy implications, requiring nuanced regulation that distinguishes humanitarian aid from religious authority formation.